Review of epidemiological and clinical characteristics and overall survival. - Helder Ferreira; Lourdes Botelho Garcia; Floristher Elaine Carrara-Marrone; Maria Cristina Bronharo Tognin; Celso Luis Cardoso (Universidade de Santa Cruz do Sul, 2014)
Backgound and Objectives: Aimed to investigate whether there is a possible association between antibiotic resistance and susceptibility to chlorhexidine of 65 clinical strains of Pseudomonas aeruginosa isolated from patients in a Brazilian hospital. Methods: The samples were identified by the MicroScan system and the sensitivity to antibiotics was performed by the disk diffusion technique. The minimum inhibitory concentration (MIC) of chlorhexidine was evaluated by broth dilution method and bactericidal activity at concentrations of 0.2% and 2%, was evaluated by the test suspension, according to the European Standard 1040. Results: All strains tested showed sensitivity to polymyxin, followed by piperacillin / tazobactam (75.4%), ceftazidime and cefepime (41.5%), tobramycin (36.9%), aztreonam and amikacin (33.8%), levofloxacin (30.8%), ciprofloxacin (29.2%), ofloxacin (27.3%), gentamicin (26.2%) and ceftriaxone (7.7%). The MIC of chlorhexidine ranged from 2.5 to 40 micrograms / ml, with MIC50 and MIC90 of 10 and 20 mg / ml. In a suspension test, the concentration of chlorhexidine in 2% destroy any bacterial cell inoculum of 65 samples. At the concentration of 0.2% chlorhexidine removed 24.2% (15/65) of samples. A sample showed reduced susceptibility chlorhexidine, ie, in the test suspension, the reduction of viable bacteria in the inoculum was less than 5 log10. Three other samples were very close to a logarithmic reduction of 5. Conclusion: In our study, the results of in vitro tests with chlorhexidine were homogeneous, seeming to indicate an association of biocide with multiple antibiotic resistance of P aeruginosa samples tested. Noteworthy is the finding of a sample of P. aeruginosa with reduced susceptibility to chlorhexidine use in dilution of 0.2%. KEYWORDS: Pseudomonas aeruginosa. Chlorhexidine. Resistance.